2014
DOI: 10.15241/sfd.4.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Historical Underpinnings, Structural Alterations and Philosophical Changes: Counseling Practice Implications of the DSM-5

Abstract: It is a pleasure to introduce this special DSM-5 edition of The Professional Counselor, which provides a solid primer regarding changes in the DSM-5 diagnosis process and how these changes will likely impact mental health professionals. Changes within the DSM-5 have prompted counselors to revisit the basics of diagnosis and consider the cessation of certain conventions (e.g., the multiaxial system) and what these changes mean to counselors as they perform their vital work for the benefit of clients. The unprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Depression was defined as either a trauma response or a mental health disorder in which people lose interest in previously enjoyed activities, feel hopeless and helpless, experience sadness, fatigue, may lack self-esteem, can appear indecisive or have difficulty making decisions, feel chronically lonely, may experience a change in sleep patterns, and may have bouts of suicidal ideation (American Psychiatric Association, 2013). Multiple studies have found that college students may experience complex trauma at high rates which can lead to a negative impact on a person's mental health (Carey et al, 2018, Frazier et al, 2009). For example, a sample of young adult women's experiences of complex trauma during childhood were correlated to symptoms of depression in young adulthood in comparison to those who did not experience complex trauma (Chapman et al, 2004).…”
Section: Depression Mental Health and Complex Traumamentioning
confidence: 99%
“…Depression was defined as either a trauma response or a mental health disorder in which people lose interest in previously enjoyed activities, feel hopeless and helpless, experience sadness, fatigue, may lack self-esteem, can appear indecisive or have difficulty making decisions, feel chronically lonely, may experience a change in sleep patterns, and may have bouts of suicidal ideation (American Psychiatric Association, 2013). Multiple studies have found that college students may experience complex trauma at high rates which can lead to a negative impact on a person's mental health (Carey et al, 2018, Frazier et al, 2009). For example, a sample of young adult women's experiences of complex trauma during childhood were correlated to symptoms of depression in young adulthood in comparison to those who did not experience complex trauma (Chapman et al, 2004).…”
Section: Depression Mental Health and Complex Traumamentioning
confidence: 99%
“…An essential element in understanding and using the DSM-5 effectively is exploring the foundational and historical roots of this complex nosology. Dailey, Gill, Karl, and Barrio Minton (2014); Gintner (2014); and Kress, Barrio Minton, Adamson, Paylo and Pope (2014) offer excellent overviews of salient changes within the DSM-5 that impact clinical practice, including how the DSM has evolved over time. While there is necessary redundancy on key points (e.g., elimination of the multiaxial format, implementation of cross-cutting symptom measures, closer alignment with the ICD coding system), each article provides an important and unique perspective.…”
Section: The Tpc Special Issue: Counseling and The Dsm-5mentioning
confidence: 99%
“…An essential element in understanding and using the DSM-5 effectively is exploring the foundational and historical roots of this complex nosology. Dailey, Gill, Karl, and Barrio Minton (2014); Gintner (2014); and Kress, Barrio Minton, Adamson, Paylo and Pope (2014) offer excellent overviews of salient changes within the DSM-5 that impact clinical practice, including how the DSM has evolved over time. While there is necessary redundancy on key points (e.g., elimination of the multiaxial format, implementation of cross-cutting symptom measures, closer alignment with the ICD coding system), each article provides an important and unique perspective.…”
Section: The Tpc Special Issue: Counseling and The Dsm-5mentioning
confidence: 99%
“…While there is necessary redundancy on key points (e.g., elimination of the multiaxial format, implementation of cross-cutting symptom measures, closer alignment with the ICD coding system), each article provides an important and unique perspective. Dailey et al (2014) offer important perceptions on changes within the DSM-5 including how changes evolved historically and the philosophical foundations behind those changes, especially those that clash with the philosophical underpinnings of counseling. The authors review the implications of such changes for professional counselors.…”
Section: The Tpc Special Issue: Counseling and The Dsm-5mentioning
confidence: 99%